Good Marketing Practices in Agricultural Vocational Training: Beiskolázási és marketing gyakorlatok bemutatása egy magyar agrárszakképző iskolán keresztül - Kis, Miklós (Acta Carolus Robertus, 2025)
As it is generally known, unemployment and the closely interconnected counterproductive and old-fashioned vocational educational systems are able to affect greatly the quality of economy. Technical and vocational schools play a huge role in avoiding this. In the course of my work I present the enrollment program and marketing tools of a vocational school, together with all its techniques and formal requirements. My goal was to look for new information collection techniques and school marketing tools necessary for enrollment, and to improve the existing ones. In my opinion, in the future, secondary schools should not think of eighth graders as "raw materials", but as "consumers". In today’s world, the 14-16 year olds are no longer the same as they were 20-30 years ago. Although they are less independent in many areas, the acceleration of information stream forces them into more and more mature decision-making situations. Therefore, it is necessary to find out what society wants, what parents want, but above all, what the child wants from the public education institution that will be the scene of his/her growing up. Based on the surveys and experiences, I concluded that it is necessary to develop more the specific assessment of the needs of eighth graders, as well as to find the communication channels that can be used in the future for the innovative enrollment of schools. Furthermore, it is necessary to continue to open the doors of the school to society, so that they can gain an insight into the daily life of vocational training and get to know it personally or through the media.